2019
DOI: 10.1111/bjet.12842
|View full text |Cite
|
Sign up to set email alerts
|

Immersive virtual field trips in education: A mixed‐methods study on elementary students' presence and perceived learning

Abstract: The purpose of this study was to investigate the influence of immersive virtual field trips (VFTs) with head‐mounted displays (HMDs) on the presence and perceived learning. A mixed‐method approach was used to obtain an overall understanding of students' experiences with this immersive technology in an elementary classroom. Both quantitative and qualitative data were collected from 27 elementary‐school students through presence surveys and reflection papers. Statistical analyses were performed to compare immers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 47 publications
7
62
0
2
Order By: Relevance
“…that participating in Immersive Virtual Field trips with the use of HMDs in elementary classrooms enhanced students' virtual presence and motivation (Cheng & Tsai, 2019;Han, 2020). Moreover, in science, some studies showed promising results regarding IVR's applications in classrooms.…”
Section: Practitioner Notesmentioning
confidence: 99%
“…that participating in Immersive Virtual Field trips with the use of HMDs in elementary classrooms enhanced students' virtual presence and motivation (Cheng & Tsai, 2019;Han, 2020). Moreover, in science, some studies showed promising results regarding IVR's applications in classrooms.…”
Section: Practitioner Notesmentioning
confidence: 99%
“…The destination of travel in previous educational VFTs included the Arctic, Hershey's Factory, Le Louvre, and Mt. Everest (Stansbury, 2014), and topics have included animals (Han, 2019) as well as climate change (Markowitz et al, 2018), which is the topic in the present study. In this study, students participate in a VFT to Greenland in order to witness the melting ice sheet and explore the consequences of global warming.…”
Section: Virtual Field Tripsmentioning
confidence: 99%
“…This was further confirmed by a recent study that examined the use of immersive VFTs in college students’ Chinese language learning (Xie et al , 2019). Two very recent studies conducted with elementary students also found that the use of immersive VFTs significantly increased students’ perception of presence (Cheng & Tsai, 2019; Han, 2019), which enhanced students’ intrinsic motivational beliefs and diminished their test anxiety in social studies (Cheng & Tsai, 2019).…”
Section: Literature Reviewmentioning
confidence: 92%
“…While these studies either provided examples of K‐12 teachers' instructional practices or examined their use by college students, very few have examined the use of immersive VFTs in elementary classroom settings. One recent study examined elementary teacher’s instructional practices (Patterson & Han, 2019) and other studies explored elementary students’ experiences and learning with immersive VFTs (Cheng & Tsai, 2019; Han, 2019). Considering that the affordability of HMDs and increased educational VR content are expected to expand the educational possibilities of immersive VFTs for younger learners, more studies can enhance our understanding about this emerging tool in elementary classrooms.…”
Section: Purpose Of the Studymentioning
confidence: 99%
See 1 more Smart Citation